2022
DOI: 10.1192/j.eurpsy.2022.2342
|View full text |Cite
|
Sign up to set email alerts
|

Euthanasia of a person with a psychiatric disorder does not violate the European Convention on Human Rights (Mortier v. Belgium [no. 78017/17])

Abstract: This peer-reviewed article has been accepted for publication but not yet copyedited or typeset, and so may be subject to change during the production process. The article is considered published and may be cited using its DOI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…As this Law does not contain specific sanctions, the general provisions of the Criminal Code apply, resulting in a situation that any infraction, even a non-essential, administrative error, would amount to murder. Therefore, the Constitutional Court concluded that the system of penalties for physicians who do not fulfill the legal due care criteria when performing euthanasia for psychiatric patients is a violation of the constitutional principles of equality and non-discrimination ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…As this Law does not contain specific sanctions, the general provisions of the Criminal Code apply, resulting in a situation that any infraction, even a non-essential, administrative error, would amount to murder. Therefore, the Constitutional Court concluded that the system of penalties for physicians who do not fulfill the legal due care criteria when performing euthanasia for psychiatric patients is a violation of the constitutional principles of equality and non-discrimination ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the fundamental rights compliance of the Belgian Euthanasia Law, as applied to euthanasia for mental suffering caused by a psychiatric disorder, was scrutinized in two ground‐breaking court decisions 3,4 .…”
mentioning
confidence: 99%
“…In the first of these, the European Court of Human Rights examined whether a euthanasia of a 64‐year‐old woman with treatment‐resistant depression and a personality disorder had violated the state's responsibility to protect her right to life, as well as the right to respect for private and family life of her son, who had only been informed about the euthanasia after it had been performed 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The case brought before the ECtHR, Mortier v. Belgium , concerned a euthanasia of a 64-year-old woman with treatment-resistant depression and a personality disorder. 5 , 6 The appellant in the case was her son, who only learned of his mother's euthanasia the day after it was performed. He claimed a violation of the right to life and his right to respect for private and family life, guaranteed by the European Convention on Human Rights.…”
mentioning
confidence: 99%